Theoretical study of the adsorption of benzene on coinage metals - Reckien, Werner; Eggers, Melanie; Bredow, Thomas (Beilstein Journal of Organic Chemistry, 2014)
The adsorption of benzene on the M(111), M(100) and M(110) surfaces of the coinage metals copper (M = Cu), silver (M = Ag) and gold (M = Au) is studied on the basis of density functional theory (DFT) calculations with an empirical dispersion correction (D3). Variants of the Perdew–Burke–Ernzerhof functionals (PBE, RPBE and RevPBE) in combination with different versions of the dispersion correction (D3 and D3(BJ)) are compared. PBE-D3, PBE-D3(BJ) and RPBE-D3 give similar results which exhibit a good agreement with experimental data. RevPBE-D3 and RevPBE-D3(BJ) tend to overestimate adsorption energies. The inclusion of three-center terms (PBE-D3(ABC)) leads to a slightly better agreement with the experiment in most cases. Vertical adsorbate–substrate distances are calculated and compared to previous theoretical results. The observed trends for the surfaces and metals are consistent with the calculated adsorption energies.
Keywords: adsorption; benzene; coinage metals; density functional theory; dispersion correction; template

(untitled) - Hausschild, A.; Karki, K.; Cowie, B. C. C.; Rohlfing, M.; Tautz, F. S.; Sokolowski, M. (Phys. Rev. Lett., 2005)

(untitled) - Ji, W.; Lu, Z. Y.; Gao, H. J. (Phys. Rev. B, 2008)

(untitled) - Kilian, L.; Hausschild, A.; Temirov, R.; Soubatch, S.; Schöll, A.; Bendounan, A.; Reinert, F.; Lee, T. L.; Tautz, F. S.; Sokolowski, M.; Umbach, E. (Phys. Rev. Lett., 2008)

(untitled) - Romaner, L.; Nabok, D.; Puschnig, P.; Zojer, E.; Ambrosch-Draxl, C. (New J. Phys., 2009)

(untitled) - Tours, J. M.; Jones, L.; Pearson, D. L.; Lamba, J. J. S.; Burgin, T. B.; Whitesides, G. M.; Allara, D. A.; Parikh, A. N.; Atre, S. V. (J. Am. Chem. Soc., 1995)

(untitled) - Witte, G.; Wöll, C. (J. Mater. Res., 2004)

(untitled) - Barlow, S. M.; Raval, R. (Surf. Sci. Rep., 2003)

(untitled) - Umbach, T. R.; Fernandez-Torrente, I.; Ladenthin, J. N.; Pascual, J. I.; Franke, K. J. (J. Phys.: Condens. Matter, 2012)

(untitled) - Bauer, O.; Mercurio, G.; Willenbockel, M.; Reckien, W.; Schmitz, C.; Fiedler, B.; Soubatch, S.; Bredow, T.; Tautz, F.; Sokolowski, M. (Phys. Rev. B, 2012)

(untitled) - Mercurio, G.; Bauer, O.; Willenbockel, M.; Fairley, N.; Reckien, W.; Schmitz, C.; Fiedler, B.; Soubatch, S.; Bredow, T.; Sokolowski, M.; Tautz, F. (Phys. Rev. B, 2013)

(untitled) - Fiedler, B.; Reckien, W.; Bredow, T.; Beck, J.; Sokolowski, M. (J. Phys. Chem. C, 2014)

Computational Chemistry of Solid State Materials: A Guide for Materials Scientists, Chemists, Physicists and others - Dronskowski, R. (Wiley-VCH, 2005)

(untitled) - Grimme, S.; Antony, J.; Ehrlich, S.; Krieg, H. (J. Chem. Phys., 2010)

(untitled) - Grimme, S. (J. Comput. Chem., 2004)

(untitled) - Grimme, S. (J. Comput. Chem., 2006)

(untitled) - Grimme, S.; Ehrlich, S.; Goerigk, L. (J. Comput. Chem., 2011)

(untitled) - Klimes, J.; Bowler, D. R.; Michaelides, A. (J. Phys.: Condens. Matter, 2010)

(untitled) - Ruiz, V. G.; Liu, W.; Zojer, E.; Scheffler, M.; Tkatchenko, A. (Phys. Rev. Lett., 2012)

(untitled) - Dion, M.; Rydberg, H.; Schröder, E.; Langreth, D. C.; Lundqvist, B. I. (Phys. Rev. Lett., 2004)

(untitled) - Zhao, Y.; Schultz, N. E.; Truhlar, D. G. (J. Chem. Theory Comput., 2006)

(untitled) - Thonhauser, T.; Cooper, V. R.; Li, S.; Puzder, A.; Hyldgaard, P.; Langreth, D. C. (Phys. Rev. B, 2007)

(untitled) - Vydrov, O. A.; Voorhis, T. V. (J. Chem. Phys., 2010)

(untitled) - Harl, J.; Kresse, G. (Phys. Rev. B, 2008)

(untitled) - Rohlfing, M.; Bredow, T. (Phys. Rev. Lett., 2008)

(untitled) - Reckien, W.; Janetzko, F.; Peintinger, M.; Bredow, T. (J. Comput. Chem., 2012)

(untitled) - Ehrlich, S.; Moellmann, J.; Reckien, W.; Bredow, T.; Grimme, S. (ChemPhysChem, 2011)

(untitled) - Moellmann, J.; Ehrlich, S.; Tonner, R.; Grimme, S. (J. Phys.: Condens. Matter, 2012)

(untitled) - Carrasco, J.; Liu, W.; Michaelides, A.; Tkatchenko, A. (J. Chem. Phys., 2014)

(untitled) - Liu, W.; Ruiz, V. G.; Zhang, G.; Santra, B.; Ren, X.; Scheffler, M.; Tkatchenko, A. (New J. Phys., 2013)

(untitled) - Liu, W.; Carrasco, J.; Santra, B.; Michaelides, A.; Scheffler, M.; Tkatchenko, A. (Phys. Rev. B, 2012)

(untitled) - Wellendorff, J.; Kelkkanen, A.; Mortensen, J. J.; Lundqvist, B. I.; Bligaard, T. (Top. Catal., 2010)

(untitled) - Jenkins, S. J. (Proc. R. Soc. London, Ser. A, 2009)

(untitled) - Chen, W.; Cao, M.-J.; Liu, S.-H.; Lu, C.-H.; Xu, Y.; Li, J.-Q. (Chem. Phys. Lett., 2006)

(untitled) - Caputo, R.; Prascher, B. P.; Staemmler, V.; Bagus, P. S.; Wöll, C. (J. Phys. Chem. A, 2007)

(untitled) - Bilic, A.; Jeffrey, A. B.; Hush, N. S.; Hoft, R. C.; Ford, M. J. (J. Chem. Theory Comput., 2006)

(untitled) - Yildirim, H.; Greber, T.; Kara, A. (J. Phys. Chem. C, 2013)

(untitled) - Atodiresei, N.; Caciuc, V.; Blügel, S.; Hölscher, H. (Phys. Rev. B, 2008)

(untitled) - Rogers, B. L.; Shapter, J. G.; Ford, M. J. (Surf. Sci., 2004)

(untitled) - Kresse, G.; Hafner, J. (Phys. Rev. B, 1993)

(untitled) - Kresse, G.; Hafner, J. (Phys. Rev. B, 1994)

(untitled) - Kresse, G.; Furtmüller, J. (Phys. Rev. B, 1996)

(untitled) - Kresse, G.; Joubert, D. (Phys. Rev. B, 1999)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1996)

(untitled) - Hammer, B.; Hansen, L. B.; Norskov, J. K. (Phys. Rev. B, 1999)

(untitled) - Zhang, Y.; Yang, W. (Phys. Rev. Lett., 1998)

(untitled) - Rezac, J.; Hobza, P. (J. Chem. Theory Comput., 2012)

Atoms in Molecules. A Quantum Theory - Bader, R. F. W. (Oxford Science Publications/Clarendon Press, 1990)

(untitled) - Henkelman, G.; Arnaldsson, A.; Jonsson, H. (Comput. Mater. Sci., 2006)

(untitled) - Lomas, J. R.; Baddeley, C. J.; Tikhov, M. S.; Lambert, R. M. (Langmuir, 1995)

(untitled) - Xi, M.; Yang, M.; Jo, S.; Bent, B.; Stevens, P. (J. Chem. Phys., 1995)

(untitled) - Campbell, C. T.; Sellars, J. R. V. (J. Am. Chem. Soc., 2012)

(untitled) - Zhou, X. L.; Castro, M. E.; White, J. M. (Surf. Sci., 1990)

(untitled) - Syomin, D.; Kim, J.; Koel, B. E.; Ellison, G. B. (J. Phys. Chem. B, 2001)

(untitled) - Bondi, A. (J. Phys. Chem., 1964)

Homepage of the D3-correction